The Effect of CLL (Community Language Learning) Towards The Second Grade Students’ Speaking Skill at Sma NW Mataram - Nanang Sugianto (Yayasan Pendidikan Intan Cendekia, 2020)
This research was aimed to know the significant effect of CLL (Community Language Learning) towards the second grade students’ speaking skill. This research was experimental reseacrh by using pre-test and post-test design. The population of study was at second grade at SMAS NW Mataram in which consist of 3 classes. The researcher used random sampling technique to take the sample of this research. Classes were chosen as the sample were B class as experimental group consisted 14 students and A class as control group consisted of 13 students. Exprimental group was treated by using CLL (Community Language Learning) and control group was treated by science fiction strategy. The instrument that were used speaking test. Then, the score were analyzed by using statistical analysis. It showed the value of t (t-test) = 23,4 was higher than the value of (t table) = 1.711 at the significance level of 5%. Therefore, according to the result of the analysis, so that the researcher concluded that there is positive effect of CLL (Community Language Learning) towadrs the students’ speaking skill at second grade students of SMAS NW Mataram.